Classical models of urban population density. The case of Barcelona Metropolitan Area - Joan Carles Martori; Jordi Suri\~nach-Caralt (European Regional Science Association (ERSA), 2001)
In this paper, we study the classical functional forms density-distance and its relation with the suburbanization for the Barcelona Metropolitan Area. The investigation of population concentration will be based on a mesure of the population density gradients derived from the classical models of urban population density. The monocentric urban density analysis has received considerable attention in urban geography and regional science as an empirical issue as well as from a theorical standpoint. The classic study by Colin Clark (1951), followed by the work of Muth (1969) and Mills (1970, 1972), has led to an extensive body of literature dealing with empirical implementations for a wide range of metropolitan areas and cities, in different countries and moments of time. In this work we analize the classical econometric models of urban density. Some of them have been used in studies about the traffic planning and some others in theoretical models on housing market. Quantitative geography has also attempted to model the urban population density. The functions have been estimated from the data sets of Barcelona Metropolitan Area (for six periods of time, 1975-1998) and eleven subcenters whose population ranges from 50.000 to over 200.000 (for one period, 1991). The data are taken from the municipality and census tract area and population data from the Census of Population
Keywords: 330